Identification of TaBADH-A1 allele for improving drought resistance and salt tolerance in wheat (Triticum aestivum L.) - Yu, Ming; Yu, Yang; Guo, Sihai; Zhang, Mingfei; Li, Nan; Zhang, Shuangxing; Zhou, Hongwei; Wei, Fan; Song, Tianqi; Cheng, Jie; Fan, Qiru; Shi, Caiyin; et al. (Frontiers in Plant Science, 2022)
Drought and salt stress can strongly affect the growth and development of wheat. Wheat adapts to drought and salt stress through osmotic regulation. Betaine aldehyde dehydrogenase (BADH) is a key enzyme in the synthesis of betaine, an osmotic regulator. We cloned a region of the TaBADH-A1 promoter and genomic DNA that included the introns and exons, from four Chinese wheat cultivars. Following the analysis of TaBADH-A1 genomic DNA and promoter sequence polymorphisms of 4 cloned and 15 cultivars from the database, 7 haplotypes of TaBADH-A1 gene were identified. We divided the 7 haplotypes with a 254 bp insertion or deletion (indel) into two main alleles, BADH-A1a and BADH-A1b. Meanwhile, a molecular marker was developed based on the 254 bp indel of the third intron of TaBADH-A1 gene. It’s an expression levels of BADH-A1b were found to be significantly higher than those of BADH-A1a under drought and salt stress conditions. Betaine accumulation was significantly higher in wheat containing BADH-A1b compared to BADH-A1a under drought and salt stress. We also identified that the average relative germination and survival rates of wheat with the BADH-A1b allele were significantly higher than wheat with the BADH-A1a allele. The results reveal that wheat containing BADH-A1b has stronger drought and salt tolerance than wheat with BADH-A1a. Meanwhile, the geographic distribution and frequency of the TaBADH-A1 locus alleles indicate that BADH-A1a has been preferred in Chinese wheat breeding programs, while BADH-A1b, associated with favorable stress tolerance, has been neglected. The results of this study provide evidence for an excellent candidate allele for marker-assisted selection of new wheat varieties with increased salt tolerance and drought resistance.